Are psychological belief built on the ideology of early christian fathers? [¿Se basan las creencias psicológicas en la ideología de los padres de la iglesia cristiana temprana?] - García Cadena, Cirilo (2019)
ABSTRACT The aims of the present study were to investigate the relationship between: a) Patristic ideology and mentalist and behaviorist beliefs, and b) the relationship between mentalist and behaviorist beliefs and cognitive, neuropsychological and interbehavioral beliefs. The beliefs were assessed through an instrument purposely built for this research. A sample composed of 284 university students of first-semester psychology (84 men and 200 women; mean ages M = 17.82 years, SD = 2.34, range 16-38 years) were enrolled. After performing structural equation modelling (SEM), results show that patristic ideology is not related to behaviorism (β = .09, p = .387), but it is related with mentalism (β = .26, p = .042), also the mentalism is related with cognitive beliefs (β = .72, p =.001) and neuropsychological beliefs (β = .87, p = .014), while behaviorism is related with interbehavioral beliefs (β = .42, p = .014). It was found that first-year psychology students show less acceptance of the early patristic ideology (M = 75.28), it is less successful than mentalism (M = 86.33). The conclusion is that mentalism, successor of Patristic ideology, continues to be related to cognitive and neuropsychological beliefs.